CO2 fluxing and carbon assimilation by arc melts during magma–limestone interaction - Frances M. Deegan; Manfredo Capriolo; Valentin R. Troll; Franz A. Weis; Sara Callegaro; Simone Colucci; Carmela Freda; Valeria Misiti; László E. Aradi; Henrik Skogby; Herlan Darmawan; Harri Geiger (Chemical Geology, 2026)

AdriE: a high-resolution ocean model ensemble for the Adriatic Sea under severe climate change conditions - Davide Bonaldo; Sandro Carniel; Renato R. Colucci; Cléa Denamiel; Petra Pranić; Fabio Raicich; Antonio Ricchi; Lorenzo Sangelantoni; Ivica Vilibić; Maria Letizia Vitelletti (Ocean Science, 2025)
The Adriatic Sea (eastern Mediterranean Basin) is traditionally considered a natural laboratory for studying a number of oceanographic processes of global interest, including coastal dynamics, dense water formation, and thermohaline circulation. More recently, the intensification of the effects of climate change and the increasing awareness of its possible consequences on the natural and socio-economic assets of the Adriatic Basin have opened new research questions and reframed most of the existing ones into a multi-decadal timescale. In this perspective, a description of the possible evolution of the physical oceanographic processes is one of the key requirements for addressing the multi-disciplinary challenges set by climate change, but up to now it has not been possible to combine, for this basin, a sufficiently high resolution in the process description with an estimate of the uncertainty associated with the predictions. This work presents an ensemble modelling approach (AdriE – Adriatic Sea Ensemble) for the kilometre-scale description of hydrodynamics in the Adriatic Sea in an end-of-century time frame. Addressing 3D circulation and thermohaline dynamics within the Regional Ocean Modelling System (ROMS), the ensemble consists of six climate runs encompassing the period from 1987 to 2100 in a severe RCP8.5 scenario forced by the SMHI-RCA4 regional climate model, driven by as many different CMIP5 general climate models made available within the EURO-CORDEX initiative. The climate ensemble is flanked by a dedicated evaluation run for the 1987–2010 period, in which SMHI-RCA4 has been driven by reanalysis fields approximating the best available boundary conditions, thus isolating the intrinsic sources of uncertainty in the RCA4–ROMS modelling chain. In order to allow a direct comparison, the assessment of the model skills in the evaluation run borrows, as far as possible, data and approaches used for the evaluation of a recent kilometre-scale, multi-decadal modelling effort for this region. The model performances are mostly aligned with the state-of-the-art reference. In particular, good results in describing the main features of marine heatwaves and cold spells, such as timing, intensity, and interannual variability, indicate that the AdriE ensemble can effectively be used for studies on the occurrence and effects of thermal extremes in the basin. Future projections suggest an increase in temperature and salinity at upper and intermediate depths, resulting in an overall decrease in water density and possibly in deep ventilation rates. Projected variations are stronger in summer and autumn, and in these seasons the ensemble range is larger than the spatial variability of the quantities and occasionally comparable with the intensity of the climate signal, highlighting the importance of an ensemble approach to treat the climate variability at this timescale. The dataset presented in this study, which can be used for the analysis of coastal and continental margin processes of general interest, is fully available upon request to the corresponding author, and monthly averages of the main quantities are available for each run on a dedicated Zenodo repository.

Scratching beneath the surface: Using Ground-Penetrating Radar to disentangle pronival ramparts, embryonic rock glaciers and moraines (Gardetta Plateau, Southwestern Alps) - Adriano Ribolini; Emanuele Forte; Varun Khajuria; Renato R. Colucci; Luca Paro; Mauro Guglielmin (Geomorphology, 2025)

200 years of equilibrium-line altitude variability across the European Alps (1901−2100) - Manja Žebre; Renato R. Colucci; Filippo Giorgi; Neil F. Glasser; Adina E. Racoviteanu; Costanza Del Gobbo (Climate Dynamics, 2021)
Mountain glaciers are key indicators of climate change. Their response is revealed by the environmental equilibrium-line altitude (ELA), i.e. the regional altitude of zero mass balance averaged over a long period of time. We introduce a simple approach for distributed modelling of the environmental ELA over the entire European Alps based on the parameterization of ELA in terms of summer temperature and annual precipitation at a glacier. We use 200 years of climate records and forecasts to model environmental ELA from 1901 to 2100 at 5 arcmin grid cell resolution. Historical environmental ELAs are reconstructed based on precipitation from the Long-term Alpine Precipitation reconstruction (LAPrec) dataset and temperature from the Historical Instrumental climatological Surface Time series of the greater Alpine region (HISTALP). The simulations of future environmental ELAs are forced with high-resolution EURO-CORDEX regional climate model projections for the European domain using three different greenhouse gas emissions scenarios (Representative Concentration Pathways, RCP). Our reconstructions yielded an environmental ELA across the European Alps of 2980 m above sea level for the period 1901−1930, with a rise of 114 m in the period 1971−2000. The environmental ELA is projected to exceed the maximum elevation of 69%, 81% and 92% of the glaciers in the European Alps by 2071−2100 under mitigation (RCP2.6), stabilization (RCP4.5) and high greenhouse gas emission (RCP8.5) scenarios, respectively.

Pros and Cons in Helicopter-Borne GPR Data Acquisition on Rugged Mountainous Areas: Critical Analysis and Practical Guidelines - E. Forte; M. Basso Bondini; A. Bortoletto; M. Dossi; R. R. Colucci (Pure and Applied Geophysics, 2019)

Anti-inflammatory effect of a novel locally acting A2A receptor agonist in a rat model of oxazolone-induced colitis - L. Antonioli; A. El-Tayeb; C. Pellegrini; M. Fornai; O. Awwad; G. Giustarini; G. Natale; L. Ryskalin; Z. H. Németh; C. E. Müller; C. Blandizzi; R. Colucci (Purinergic Signalling, 2018)

The Triglav Glacier (South-Eastern Alps, Slovenia): Volume Estimation, Internal Characterization and 2000–2013 Temporal Evolution by Means of Ground Penetrating Radar Measurements - Costanza Del Gobbo; Renato R. Colucci; Emanuele Forte; Michaela Triglav Čekada; Matija Zorn (Pure and Applied Geophysics, 2016)

Precipitation–temperature changes and evolution of a small glacier in the southeastern European Alps during the last 90 years - Renato R. Colucci; Mauro Guglielmin (International Journal of Climatology, 2015)
Very small glaciers (area 2 ) have received increased scientific attention during recent years, both for their rapid responses to the climate forcing and because they are characterized by microclimatic conditions, often marginal to glacier formation. They are particularly sensitive to climate changes and characterized by a great mass turnover, particularly evident in maritime areas with high precipitation. Here we consider the evolution from 1920 of the ‘Canin Eastern Glacier’ (Italian Southeastern Alps) in order to correlate its evolution to the precipitation–temperature trends. We reconstructed a precipitation–temperature record at the altitude of the glacier, filling a lack of knowledge in this alpine sector. We observed a decrease in the mean annual precipitation of 10% in 90 years and a warming trend of 0.1°C decade −1 since 1851, and of 0.7°C decade −1 in the last 20 years. An inverse correlation between precipitation and mean air temperature during summer and ablation periods was also observed. Glacier dynamics revealed a phase of stability between 1945 and 1985 that seems to be a peculiar characteristic of this area. Moreover, through a general regression model the glacial terminus variations seem to be statistically influenced only by winter precipitation. This fact opens interesting perspectives for the possible future evolution of this small glacier and, more in general, to other small glaciers in maritime areas in regard to climate change scenarios.

First record of the genus Dermatobranchus van Hasselt, 1824, in the Mediterranean Sea (Nudibranchia: Arminidae) - G. COLUCCI; R. STRAFELLA; E. TRAINITO; M. DONEDDU (Mediterranean Marine Science, 2015)
Three individuals of a nudibranch belonging to the genus Dermatobranchus (Arminidae) were found at a depth of 3 meters, in a bottom with sand and gravel, during night SCUBA diving activity in Porto Pirrone, Leporano (Taranto, Apulia, Italy). The external morphology and coloration of these Mediterranean individuals clearly resemble those of D. rubidus (Gould, 1852), a species known only from the central and western Pacific Ocean. This is the first record of the genus Dermatobranchus van Hasselt, 1824 for the Mediterranean Sea.

Evaluation of Internal Structure, Volume and Mass of Glacial Bodies by Integrated LiDAR and Ground Penetrating Radar Surveys: The Case Study of Canin Eastern Glacieret (Julian Alps, Italy) - R. R. Colucci; E. Forte; C. Boccali; M. Dossi; L. Lanza; M. Pipan; M. Guglielmin (Surveys in Geophysics, 2015)

Mechanisms of protection by pantoprazole against NSAID-induced gastric mucosal damage - M. Fornai; G. Natale; R. Colucci; M. Tuccori; G. Carazzina; L. Antonioli; S. Baldi; V. Lubrano; A. Abramo; C. Blandizzi; M. Del Tacca (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)